Characterization and health risk assessment of chemical and microbial pollutants in particulate matter from dust prone regions - Fatima Mahroos; Shahd Habiba; Imene K. Lazreg; Sofian Kanan; Fatin Samara (Scientific Reports)
Abstract Increasing anthropogenic contributions to desert dust storms have raised significant public health concerns, particularly in arid/semi-arid regions. This study investigated particulate matter (PM) composition in an arid environment, focusing on organic, heavy metal, and microbial contaminants, along with comprehensive health risk assessments. ICP-OES analysis of inorganic matter showed moderate concentrations (> 8.21 µg/g) of Ca, Fe, Al, S, Mg, and Rb, while K, Cu, P, and Na were detected at low concentration levels, along with other trace metals. GC-MS analysis identified 11 targeted polycyclic aromatic hydrocarbons (PAHs), including phenanthrene, benzo[b]fluoranthene, and chrysene. Several organic pollutants, including some from the PFAS group, were detected in the samples. 16 S rRNA sequencing identified seven bacterial species, including Enterococcus faecium, Staphylococcus spp., and Acinetobacter radioresistens. Toxicity calculations indicated no significant lung cancer risk associated with PAHs, with further calculations suggesting minimal population-level risks. However, heavy metal risk metrics indicated greater non-carcinogenic risks than carcinogenic ones. The microbial species identified predominantly belonged to risk groups 1 and 2, representing opportunistic, infection-causing pathogens. This study highlights the necessity for a multidisciplinary approach to analyze complex dust particle constituents and their potential health impacts and calls for targeted air quality management policies to mitigate public health risks.